2020
DOI: 10.3390/ma13245696
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humidity on the Elastic Modulus and Axis Compressive Strength of Concrete in a Water Environment

Abstract: Concrete structures are often in different humidity conditions that have a significant impact on the elastic modulus of concrete, therefore, systematic research on the evolution of the law of concrete elastic modulus under different humidity conditions is needed. In this study, the variation laws of the water saturation of concrete specimens with strength grades C15, C20, and C30 were obtained, and then the influence laws of the water saturation on the concrete axial compressive strength were carried out, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was discovered that impregnated concrete exhibits greater values of Poisson's ratio and modulus of elasticity compared to dry concrete with equivalent volumes [41]. In [42], it was found that the modulus of elasticity of totally impregnated concrete exhibited a 30% increase compared to that of fully dry concrete. The modulus of elasticity of dry concrete exhibits a 15% reduction compared to impregnated concrete.…”
Section: Wwwetasrcom Ihteshaam and Jin: A Comprehensive Literature Re...mentioning
confidence: 99%
“…It was discovered that impregnated concrete exhibits greater values of Poisson's ratio and modulus of elasticity compared to dry concrete with equivalent volumes [41]. In [42], it was found that the modulus of elasticity of totally impregnated concrete exhibited a 30% increase compared to that of fully dry concrete. The modulus of elasticity of dry concrete exhibits a 15% reduction compared to impregnated concrete.…”
Section: Wwwetasrcom Ihteshaam and Jin: A Comprehensive Literature Re...mentioning
confidence: 99%
“…It is important to mention that all cases are considered for plane strain, therefore; there is no consideration to the out of plane direction (i.e., 2D case). Moreover, the change in mechanical properties due to the physical and chemical [84][85][86] interaction with the hydrogen bonds of water is beyond the scope of this research. These two studies are discussed in Sections 4.1, and 4.2, respectively.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Compared with the thermal weakening effect of the elastic modulus, the water effect on the elastic modulus is still controversial. Although most studies show that water has a strengthening effect on the elastic modulus due to its smaller compressibility and greater viscosity than air [18][19][20][21][22][23], some scholars still believe that the influence of water on the elastic modulus is not significant [24,25], and may even go down [26]. The reason for the insignificant influence of water on the elastic modulus or even the weakening effect may be that the initial cracks inside the concrete are too many due to uneven mixing in the process of concrete production or the relatively low environmental humidity in the process of concrete curing.…”
Section: Introductionmentioning
confidence: 99%